2012
DOI: 10.1016/j.jcrs.2011.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of variables affecting intraoperative aberrometry

Abstract: Dr. Olson has been a consultant to Abbott Medical Optics, Inc., Becton, Dickinson and Co., and Allergan, Inc., and has received grant support from Abbott Medical Optics, Inc. and Allergan, Inc. No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 3 publications
2
21
0
4
Order By: Relevance
“…In a previous case series of 10 eyes 1 h after cataract surgery, measurement success was as low as 25% 14. Similarly, we were successful in all three attempted measurements during aphakia in only 30 out of 64 eyes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In a previous case series of 10 eyes 1 h after cataract surgery, measurement success was as low as 25% 14. Similarly, we were successful in all three attempted measurements during aphakia in only 30 out of 64 eyes.…”
Section: Discussionsupporting
confidence: 69%
“…In our previous study13 changing the posture from seated to supine led to cyclotorsion and apparently also to a myopic SE shift. Second, the lid speculum may be responsible for significant changes in cylinder power and axis depending on how much the patient squeezed 14. Third, varying corneal wound integrity and hydration may lead to an altered corneal curvature, resulting in significant changes of refraction.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study of its kind and showed that the ACD intraOP with a continuous intraoperative OCT device is a useful parameter for IPC. Other attempts, to calculate the IOL power using intraoperative measurements showed little success: intraoperative autorefraction has problems, such as misalignment, or insufficient patient fixation,18 and intraoperative wavefront aberrometry was found to be too inaccurate for IPC 19. Additionally, the main source of error, namely predicting the postoperative IOL position4 remains.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technology was found to be inaccurate for this purpose due to several problems, such as residual viscoelastics in the anterior chamber and tear film problems. 23 Additionally, these methods have the same problem as conventional IOL power calculation formulae: they use fudge factors to predict the postoperative IOL position as well as the postoperative ACD shift. This study showed that continuous intraoperative measurements of the lens capsule after removing the lens were a powerful tool to predict the postoperative IOL position.…”
Section: Discussionmentioning
confidence: 99%